Exploring how the urban neighborhood environment influences mental well-being using walking interviews. (January 2021) - Lauwers, Laura; Leone, Michael; Guyot, Madeleine; Pelgrims, Ingrid; Remmen, Roy; Van den Broeck, Kris; Keune, Hans; Bastiaens, Hilde
Abstract: Mental well-being in cities is being challenged worldwide and a more detailed understanding of how urban environments influence mental well-being is needed. This qualitative study explores neighborhood factors and their interactions in relation to mental well-being. Individual semi-structured walking interviews were conducted with 28 adults living in the Brussels-Capital Region. This paper provides a detailed description of physical neighborhood factors (green-blue spaces, services, design and maintenance, traffic, cellphone towers) and social neighborhood factors (neighbor ties, neighbor diversity, social security) that link to mental well-being. A socio-ecological framework is presented to explain interactions among those neighborhood factors, and personal and institutional factors, in relation to mental well-being. The findings are linked to existing concepts and theories to better understand the mechanisms underlying the associations between the urban neighborhood environment and mental well-being. Finally, implications of the walking interview method are discussed. Highlights: Personal, social, physical, and institutional factors describe the influences of the neighborhood on mental well-being. A socio-ecological framework is presented to describe the complex interplay among those factors. A summary of concepts and theories helps to understand the underlying mechanisms. Walking interviews can support participatory planning to detect complex interactions in the neighborhood environment.